Mystery of Turkish motives (Eurasian Journal of Philology Science and Education, 2016)
In general, in the world literature, very often there are such well-known characters of the «Book of my grandfather Korkut» as tepegoz and Bisat and motifs associated with them. Thus, the author of the article examining the importance of story value associated with Polyphemus from Greek mythology, turns its attention to the nature and history of the spread of this mythological motif. Starting with the «1000 Nights», the famous Turkic people stories from epics such as «Shahnameh», «Oguzname», «Koroglu», Kazakh folklore and mythological prose samples are ubiquitous motifs similar to the story of tepegoz. The researcher compares not only the general theme of the East and the West, but by the analysis of this plot shows the character of its development and dissemination. Also used valuable materials scientists such as Herodotus, Ch Valikhanov, Dolgat W., H. Koroglu. Raised in an article addressed to the problem of cultural continuity and development of artistic traditions.
Keywords: folklore; story; motive; legend; genre; pattern; tradition; epic; epos; prose